Heat Stroke in Physical Activity and Sports (English original version) - Yuri Hosokawa; William M Adams; Rebecca L Stearns; Douglas J Casa (Pensar en Movimiento)
Exertional heat stroke (EHS) is one of the leading causes of sudden death in sport and physical activity. In American Football alone, there have been 46-documented EHS fatalities in the United States between 1995-2010.  In 2003, National Collegiate Athletics Association mandated pre-season heat acclimatization guidelines, which successfully decreased the number of heat stroke fatalities in collegiate American football. However, despite the advancement in modern medical care and increased awareness in heat safety, lack of appropriate on-site medical care is still contributing to EHS seen especially in the youth level. It is well established in scientific literature that fatalities as a result of EHS are largely preventable with proper education on the knowledge of recognition, treatment, and prevention of EHS. This document provides a review of the current best medical practices and evidence on the epidemiology, pathophysiology, risk factors, recognition, treatment, prevention, and return to play recommendations for EHS, specifically as they relate to sport and physical activity.